Aromatase inhibitor use during ovarian stimulation suppresses growth of uterine endometrial cancer in xenograft mouse model. Issue 2 (28th December 2017) - Kawahara, Tai; Okamoto, Naoki; Takae, Seido; Kashiwagi, Megumi; Nakajima, Mariko; Uekawa, Atsushi; Ito, Junya; Kashiwazaki, Naomi; Sugishita, Yodo; Suzuki, Nao
Abstract: STUDY QUESTION: Could aromatase inhibitors (AI) be used to reduce risks of uterine endometrial cancer growth or recurrence during ovarian stimulation? SUMMARY ANSWER: In a xenograft mouse model of endometrial cancer, concomitant AI administration suppressed the growth of endometrial cancer during ovarian stimulation. WHAT IS KNOWN ALREADY: Recurrence and mortality rates of estrogen receptor-positive early breast cancer are reduced by long-term AI administration. Concomitant AI use for ovarian stimulation in patients with breast cancer is recommended for reducing estrogen-related potential risks. However, the efficacy of concomitant AI use for estrogen receptor-positive endometrial cancer have not been demonstrated conclusively by clinical or experimental animal studies. STUDY DESIGN, SIZE, DURATION: Forty nude mice xenografted with uterine endometrial cancer cells were allocated to four groups. Group 1: no ovarian stimulation (control). Group 2: ovarian stimulation. Group 3: AI administration + ovarian stimulation. Group 4: ovariectomy and ovarian stimulation. Tumor growth was evaluated during the 6-week treatment period. PARTICIPANTS/MATERIALS, SETTING, METHODS: Ishikawa 3-H-12 uterine endometrial cancer cells (estrogen and progesterone receptors-positive) were transplanted into 6-week-old BALB/cS lc-nu/nu nude mice, followed by interventions 2 weeks later. MAIN RESULTS AND THE ROLE OF CHANCE: Compared to ovarian stimulation alone (Group 2), significant suppressions of tumor growth were observed in other three groups (Groups 1, 3 and 4, all at P < 0.05) and correlated with estrogen levels. AI administration had no apparent impact on embryo development. LIMITATIONS, REASONS FOR CAUTION: In this study, we examined the growth of endometrial cancer tumors using one endometrial cancer cell line. Clinical endometrial cancer or hyperplasia cells can have diverse origins and AI may not be effective against other cancer cell types. WIDER IMPLICATIONS OF THE FINDINGS: Concomitant AI use may provide a chance for safer childbirth by for patients with endometrial cancer or hyperplasia. STUDY FUNDING/CONPETING INTEREST(S): This study was supported by the Graduate Student Aid from the St. Marianna University School of Medicine. The authors declare no competing interests.